2007
DOI: 10.2215/cjn.02560607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors in Diabetic Nephropathy

Abstract: Several genes that predispose to type 2 diabetes have recently been identified. In addition to the recognized and powerful effects of environmental factors, there is abundant evidence in support of genetic susceptibility to the microvascular complication of nephropathy in individuals with both type 1 and type 2 diabetes. Familial aggregation of phenotypes such as end-stage renal disease, albuminuria, and chronic kidney disease have routinely been reported in populations throughout the world, and heritability e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 76 publications
3
129
1
Order By: Relevance
“…In accordance with our current understanding [29,30], we observed the important causal effects of lipid, RAS and glycaemia on renal function in the low-risk model, and of BP and NOS/MMP3 genotypes in the high-risk model. Several chromosomal regions linked to diabetic kidney disease contain candidate genes, including the CNDP1, ADIPOQ, ELMO1, SOD2, ACE and NOS3 [18]. In support of these findings, we have quantified the effects of the RAS and NOS genotypes on renal function in both models.…”
Section: Effects Of Genotypes and Phenotypes On Renal Functionmentioning
confidence: 56%
See 1 more Smart Citation
“…In accordance with our current understanding [29,30], we observed the important causal effects of lipid, RAS and glycaemia on renal function in the low-risk model, and of BP and NOS/MMP3 genotypes in the high-risk model. Several chromosomal regions linked to diabetic kidney disease contain candidate genes, including the CNDP1, ADIPOQ, ELMO1, SOD2, ACE and NOS3 [18]. In support of these findings, we have quantified the effects of the RAS and NOS genotypes on renal function in both models.…”
Section: Effects Of Genotypes and Phenotypes On Renal Functionmentioning
confidence: 56%
“…The strength of the relationships between the explanatory factors and outcome variable is indicated by the path coefficients (5) glucotoxicity, lipotoxicity, inflammation and haemodynamic abnormalities cause renal damage [18].…”
Section: Introductionmentioning
confidence: 99%
“…Asian and Hispanic patients have the highest prevalence of albuminuria (55%), while Caucasians have the lowest (40.6%) [3], indicating possible ethnic differences. The pathogenesis of DN is multifactorial, and thought to come about as a result of environmental and genetic factors [4]. Genetic factors play an important role in the observed ethnic disparity in the development of DN [4], and gender may predispose patients to the development of kidney disease, as both animal and human studies have reported a higher incidence and a faster progression rate of the disease among males [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…19 -23 Nevertheless, the genetic component of the pathophysiologic process of DN has not yet been deciphered. 24 Because numerous genetic and environmental factors, along with their interactions, are considered to be implicated in the pathogenesis of DN, polymorphisms of individual genes are expected to confer a modest risk to susceptibility of DN.Genetic association studies that examined whether variants in eNOS gene are associated with DN or with diabetes leading to severe nephropathy (DSN) have yielded conflicting or inconclusive results. The lack of replication might be due to small sample sizes, different populations, sampling strategies, genotyping procedures, and number of loci included in the studies.…”
mentioning
confidence: 99%